Phenology and seed germination improvement of two important tree species in the moist semi-deciduous forest zone of Ghana - Amponsah, James Oppong (2016)
A thesis submitted to the School of Research and Graduate Studies, Kwame Nkrumah University of Science and Technology (KNUST), Kumasi, in partial fulfilment of the requirements for the degree of Master of Philosophy (Seed Science and Technology)